Weathering Classes In Relation To Physical And Mechanical Properties Of Decomposed Granite - Ab Han, Norfateha (Universiti Sains Malaysia, 2018)
The main challenges in the study of slope stability, foundation, underground openings and excavation of rocks are by understanding the degree of weathering. The weathering profile at certain area are usually graded based on field observation, geological studies and material properties of the rocks. The research is on the decomposed granitic which are classified according to the degree of weathering and its properties. Based on earlier studies, decomposed granite is referring from grade II to grade V of weathering grade. This research focused on the relationship between the characteristics of weathering grade of granite and its properties. A series of physical and mechanical tests are carried out to identify the physical and mechanical properties of decomposed granite. The physical tests consist of the particle size distribution analysis, moisture content test, Atterberg limit test and specific gravity test which give result of 2.6 whereas mechanical test consist of direct shear test, point load test and aggregate crushing test. X-ray fluorescence (XRF) analysis are carried out to analyze the chemical composition in each weathering grade that significantly affect the properties of granite. The result from data analysis shows the correlation between the weathering grade of decomposed granite and as the weathering degree changes, the properties of granite changes. The R2 coefficient for moisture content, liquid limit, point load index and aggregate crushing test was 96.06%, 93.7%, 49.21% and 92.74%. The composition of SiO2 with hardness 7 out of 10 in Mohr hardness scale are decreased as the weathering rate of granite increase. To conclude, the weathering grade affected the physical and mechanical properties of granitic rock.